Participation in just transition – gaps in applying deliberative governance in coal regions of Greater Poland, Lodzkie, Lower Silesia and Silesia - Drobniak, Adam; Rogowska-Sawicz, Małgorzata (Rozwój Regionalny i Polityka Regionalna, 2025)
The paper explores the use of proactive participation tools in strengthening a deliberative governance (DG) within transition planning for coal regions. The main research question is: to what extent was the planning of the just transition in Polish Coal Regions (PCRs) based on the proactive participation postulated in the DG approach? Proactive participation, as applied in the case of PCRs supported by the Just Transition Fund (JTF) – including Eastern Greater Poland, the Walbrzych Subregion, the Belchatów Area of Transition (BAT), and the Silesian coal regions – have encountered a number of barriers during the programming of the Territorial Just Transition Plans (TJTPs). Therefore, the aim of the paper is to indicate the gaps in participatory practices during the programming of TJTPs for PCR that limit the DG. The study employs a focused comparison framework (FCF), combining a conceptual analysis of DG in context of detailed review of participatory instruments used in TJTPs across the PCRs. The methodology draws on the Horizon DUST project framework including in-depth interviews with policymakers and decision-makers in the four PCRs. The main findings highlight a detailed typology of gaps to proactive participation identified in the surveyed regions, including a limited range of participatory instruments, poor use of digital tools, lack of direct citizen involvement, insufficient consideration of local and sub-local levels, and the unsatisfactory commitment of public authorities.